แนวทางการออกแบบภูมิทัศน์เมืองเพื่อการสัญจรในพื้นที่ย่านราชดำเนินกลาง - ปริญญาพร ศรีวรนันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
"Urbanscape for Wayfinding" consists of the physical components that contribute to the understanding of the area for the people who are moving through as well as moving to that particular area. This article is a summary of the research on Design Guidelines for Wayfinding in Central Ratchadamneon area, where is an important heritage district occupied by various of groups of people, especially the tourists who are not familiar with the traffic in this area. The key findings of this research conclude that in order to have the better Urbanscape for Wayfinding, there must be a high-efficiency local linkage. Importantly, this local linkage must have a well-established relationship with the urban traffic as a whole. Successful design to promote wayfinding should have suitable and diverse land use as well as the landscape and buildingscape that allow diverse groups of commuters a continual access. For examples, there should be a proper ratio of the building height to the road width suitable for the use of that area; the proportion or the height of podium should be relatable to human scale to create a walking environment; the buildings and the voids should be regulated suitably to be built-to-line in order to create a clear street façade; provide the building height transit zone to maintain the overview of the district; provide a harmonious and continuous building façade; provide a continuous structure that shelters from weather to create the walkable experience and the interaction between the buildings and the pedestrian way; provide street furniture including information and street signs and plants that do not obstruct visibility.